Superior Room Temperature Compressive Plasticity of Submicron Beta‐Phase Gallium Oxide Single Crystals. (25th September 2022) - Wu, Yueqin; Rao, Qijian; Best, James P.; Mu, Dekui; Xu, Xipeng; Huang, Han
Abstract: Bulk‐scale ( 2 ¯ 2 01)‐oriented monoclinic beta‐phase gallium oxide (β‐Ga2 O3 ) single crystals are brittle and fracture at low compressive strains. Here, it is reported that submicron β‐Ga2 O3 pillars exhibit an exceptional room temperature plastic strain of up to ≈22% under compression. Deformation is observed in transition from brittle to superior plasticity with reduction of pillar size. The critical diameter for the brittle to ductile transition is ≈800 nm, attributed to the initiation of dislocation slip on the primary (400) slip planes. Below 500 nm, a second transition is reported to superior plastic deformation, achieved through the activation of secondary mechanisms due to both deconfinement and low crystalline symmetry of β‐Ga2 O3, differentiating this finding from size‐effected plasticity of other brittle materials where plasticity is attributed to dislocation slip on primary slip planes. Molecular dynamics simulation supports the proposed mechanism of pillar deconfinement where plastic deformation in larger pillars is solely dominated by planar defects on (400) slip planes, while secondary defects are induced for sufficiently small pillars. No plasticity is observed for equally dimensioned pillars tested on a (010)‐oriented surface, highlighting the importance of presenting crystallography on submicron plasticity in this material. Abstract : Superior plasticity of monoclinic beta‐phase gallium oxide β‐Ga2 O3 single crystals is observed for micropillar diameters <500 nm due to lateral deconfinement and low crystal symmetry. The ultra‐high plasticity of this eminently brittle material is desirable for flexible electronic device applications. The observed superior plasticity opens opportunities to further study and leverage semiconductors with low symmetry crystal structures.